Mode characteristics of silver-coated inverted-wedge silica microdisks - Bo, Fang; Wang, XiaoOu; Li, Ying; Gao, Feng; Zhang, GuoQuan; Xu, JingJun (Science China. Physics, mechanics & astronomy, 2015)
The characteristics of whispering gallery modes （WGM） in silver-coated inverted-wedge silica microdisks are theoretically in- vestigated by using finite element method. Dielectric TE mode always exists in silver-coated inverted-wedge resonators; die- lectric TM mode tends to couple with SPP modes; only pure interior surface plasmonic polariton （SPP） mode but not pure ex- terior SPP mode is observed in contrast to the metal-coated cylindrical and toroidal resonators. The dependence of quality fac- tor of different kinds of WGMs on the radius of the resonator and the thickness of the coated silver layer are systematically an- alyzed. We find that the quality factors of the hybrid WGMs associated with SPP mode can reach 104. The maximum light in- tensity enhancement in ambient for a hybrid mode consisting of a dielectric TM mode and an exterior SPP mode can be ob- tained when a silver film of thickness -40 nm is deposited. The silver-coated inverted-wedge silica resonators may be widely applied in sensing and surface enhanced Raman scattering.